Seroprevalence of anti-SARS-CoV-2 antibodies and risk factors among healthy blood donors in Fayoum, Egypt - Abeer Abdelrazik; Rhogenie Sauza; Hossam Abdelaziz (Egyptian Journal of Medical Research, 2023)
Background: More eligibility criteria have been added for blood donors to warrant safety of blood donations during the COVID-19 pandemic. The aim of this study was to assess the seroprevalence of antibodies to SARS-CoV-2 among blood donors and to study the lifestyle of asymptomatic cases.Methods: One thousand, three hundred twelve voluntary blood donors were enlisted in this study in the University Hospital from September to December 2021. Samples were tested for SARS-CoV-2 antibody. Donor’s lifestyle was analyzed.  Results: 95.4% of the studied group were males, the seroprevalence of SARS-CoV-2 antibody was 83.3% and related to gender, regular donation, type of donation, and more frequent when donors shared transport and accommodation. 9.5% were found to possess cough/fever or a history of contact with COVID-19 patients.  Conclusion: Blood donors proved to give an idea about virus spreading among healthy population.  Additional risk factors can be identified to ensure safety of transfusion.